The Curvilinear Relationship between Age and Emotional Aperture: The Moderating Role of Agreeableness - Faber, Anna; Walter, Frank (Frontiers in Psychology, 2017)
The capability to correctly recognize collective emotion expressions (i.e., emotional aperture) is crucial for effective social and work-related interactions. Yet, little remains known about the antecedents of this ability. The present study therefore aims to shed new light onto key aspects that may promote or diminish an individual’s emotional aperture. We examine the role of age for this ability in an online sample of 181 participants (with an age range of 18 to 72 years, located in Germany), and we investigate agreeableness as a key contingency factor. Among individuals with lower agreeableness, on the one hand, our results indicate a curvilinear relationship between age and emotional aperture, such that emotional aperture remains at a relatively high level until these individuals’ middle adulthood (with a slight increase until their late 30s) and declines afterwards. Individuals with higher agreeableness, on the other hand, exhibit relatively high emotional aperture irrespective of their age. Together, these findings offer new insights for the emerging literature on emotional aperture, illustrating that specific demographic and personality characteristics may jointly shape such collective emotion recognition.